The Humanity Aspect of Art and Creative Process in The Midst of Industry Era 4.0 Towards The Era of Society 5.0 - Aaisyah, Sitti; Oktoriani, Duala (Universitas Bosowa, 2024)
In the era of advanced technology where Artificial Intelligence (AI) is developing so rapidly and has become an integral part of human life, its existence has many influences on how humans live their lives. The speed and convenience offered by AI comes with negative impacts such as degradation of humans' main potential (creation, taste and intention). This is possible when AI is not controlled scientifically and ethically. When civilization from the industrial era 4.0 moves towards the era of society 5.0, AI technology becomes a necessity. Changes in this era also have implications for humans in interpreting art and the creative process. It is very important to step back and review the ethical aspects of technology so that AI, which is ideally intended to help humans do better work, can be implemented wisely.